Deciphering the role of female reproductive tract microbiome in reproductive health: a review - Gao, Hong; Liu, Qiao; Wang, Xiaolan; Li, Ting; Li, Huanhuan; Li, Genlin; Tan, Lingling; Chen, Yahui (Frontiers in Cellular and Infection Microbiology, 2024)
Relevant studies increasingly indicate that female reproductive health is confronted with substantial challenges. Emerging research has revealed that the microbiome interacts with the anatomy, histology, and immunity of the female reproductive tract, which are the cornerstone of maintaining female reproductive health and preventing adverse pregnancy outcomes. Currently, the precise mechanisms underlying their interaction and impact on physiological functions of the reproductive tract remain elusive, constituting a prominent area of investigation within the field of female reproductive tract microecology. From this new perspective, we explore the mechanisms of interactions between the microbiome and the anatomy, histology, and immunity of the female reproductive tract, factors that affect the composition of the microbiome in the female reproductive tract, as well as personalized medicine approaches in managing female reproductive tract health based on the microbiome. This study highlights the pivotal role of the female reproductive tract microbiome in maintaining reproductive health and influencing the occurrence of reproductive tract diseases. These findings support the exploration of innovative approaches for the prevention, monitoring and treatment of female reproductive tract diseases based on the microbiome.